Comparison of different chelating agents to enhance reductive Cr(VI) removal by pyrite treatment procedure. (1st June 2015) - Kantar, Cetin; Ari, Cihan; Keskin, Selda
Abstract: New technologies involving in-situ chemical hexavalent chromium [Cr(VI)] reduction to trivalent chromium [Cr(III)] with natural Fe(II)-containing minerals can offer viable solutions to the treatment of wastewater and subsurface systems contaminated with Cr(VI). Here, the effects of five different chelating agents including citrate, EDTA, oxalate, tartrate and salicylate on reductive Cr(VI) removal from aqueous systems by pyrite were investigated in batch reactors. The Cr(VI) removal was highly dependent on the type of ligand used and chemical conditions (e.g., ligand concentration). While salicylate and EDTA had no or little effect on Cr(VI) removal, the ligands including citrate, tartrate and oxalate significantly enhanced Cr(VI) removal at pH < 7 relative to non-ligand systems. In general, the efficiency of organic ligands on Cr(VI) removal decreased in the order: citrate ≥ oxalate ≈ tartrate > EDTA > salicylate ≈ non-ligand system. Organic ligands enhanced Cr(VI) removal by 1) removing surface oxide layer via the formation of soluble Fe–Cr-ligand complexes, and 2) enhancing the reductive iron redox cycling for the regeneration of new surface sites. While citrate, oxalate and tartrate eliminated the formation of surface Cr (III)–Fe(III)-oxides, the surface phase Cr (III) species was observed in the presence of EDTA and salicylate indicating that Cr(III) complexed with EDTA and salicylate sorbed or precipitated onto pyrite surface, thereby blocking the access of CrO 4 2 − to pyrite surface. The binding of Fe(III) with the disulfide reactive sites (≡Fe–S–S–Fe(III)) was essential for the regeneration of new surface sites through pyrite oxidation. Although Fe(III)–S species was detected at the pyrite surface in the presence of citrate, oxalate and tartrate, Fe(III) complexed with EDTA and salicylate did not strongly interact with the disulfide reactive sites due to the formation of non-sorbing Fe(III)-ligand complexes. The absence of surface Fe(III)–S species indicated that no new reactive sites were generated through Fe redox cycling in the presence of salicylate and EDTA. Highlights: The efficiency of Cr(VI) reduction by pyrite was highly dependent on the type of ligand used. Organic ligands enhanced Cr(VI) removal by eliminating the surface oxidation products. Organic ligands enhanced the reductive iron redox cycling for surface site regeneration. The adsorbed Fe(II) played an important role on Cr(VI) reduction at the pyrite surface.